Protective effects of curcumin against chemical-induced toxicity in the male reproductive system: a systematic review - Tarlan, Mitra; Heidrizadeh, Nillofar; Gooharpoor, Sara; Tavallaei, Omid; Khazayel, Saeed; Farzaei, Mohamad Hosein; Echeverría, Javier (Frontiers in Pharmacology, 2026)
BackgroundCurcumin is a biologically active substance present in turmeric. It has recently been suggested for its protective potential against a wide variety of chemical-induced toxicities.PurposeThis systematic review aims to summarize current evidence on the protective effects of curcumin against chemical-induced toxicity, with particular emphasis on its impact on the male reproductive system.MethodsA literature search was conducted using the major databases PubMed®, Scopus®, Web of Science®, and ScienceDirect®, up to December 2024. This review encompassed studies assessing curcumin’s protective role against chemical toxicity, both in vitro and in vivo. Extracted data included the type of chemical agent, dosage, curcumin formulation, and reported toxicity outcomes.Results and discussionA total of 31 studies were included in the present review based on the established inclusion criteria. The toxicants studied contained heavy metals (lead and cadmium), pesticides (e.g., Malathion), and industrial solvents (notably titanium dioxide nanoparticles). Curcumin has demonstrated significant protective effects through multiple mechanisms, including antioxidant activity, anti-inflammatory effects, and modulation of detoxification enzymes. Interestingly, curcumin supplementation was associated with reduced oxidative stress markers and improved histopathological findings across various animal models. The effective dose varied widely across studies, with most showing positive effects at doses between 50 mg/kg and 200 mg/kg.ConclusionThe results of this systematic review suggest that curcumin holds promise for preventing various chemical-induced toxicities. Its diversified mechanisms of action show promise as a therapeutic agent for the relief of chemical toxicity. Nonetheless, additional studies are required to determine the most effective dosing strategies, examine bioavailability, and assess the safety of long-term use.